Regional development between theory and practice 2023 - Editorial (Acta Polytechnica CTU Proceedings)
Before European society could cope with the effects of the Covid-19 pandemic, new problems were arose caused by Russian aggression in Ukraine. This has brought not only new security threats and a new wave of migrants, but also new and hitherto unexpected problems in terms of energy prices and availability. All these problems must be tackled not only by Europe as a whole, by individual states, but also by every region, city, or municipality. The aim of the conference is to create a platform for the transfer of new scientific knowledge and experience, how to analyse and solve the problems that have arisen, i.e., to propose ways, tools, and innovations for dealing with their consequences.